SPONTANEOUS RETROPERITONEAL HEMATOMA IN A COVID-19 PATIENT - Sekulić, Ana D; Marinkovic, Olivera; Mrda, Davor; Toskovic, Borislav; Zdravkovic, Marija; Djuran, Predrag (Srpski medicinski časopis Lekarske komore, 2021)
Introduction: The infection caused by the SARS-CoV-2 virus is known to cause a hypercoagulable condition resulting in acute thrombotic events. Thromboembolic events occur in as many as 21.0% of cases with a mortality rate of about 74.0% in persons infected with COVID-19. Anticoagulant therapy is used in severeCOVID-19 infections in order to prevent thrombosis and has been shown to reduce mortality. The use of anticoagulants is not without risks. Bleeding complications can range from mild to severe or even life-threatening, such as retroperitoneal bleeding into the psoas muscle.Case report: We present a case of a patient who developed a complication of bleeding into the retroperitoneal space during the treatment of bilateral bronchopneumonia caused by the SARS-CoV-2 virus. After the diagnosis was established, on the basis of a clinical examination, laboratory and radiological examinations, and after initial conservative treatment at the UHMC Bežanijska kosa, the patientunderwent embolization of the left lumbar arteries from the right inguinal fossa, during procedural analgosedation. After the radiological procedure, the recovery was satisfactory, but due to the impossibility of resorption of an encapsulated hematoma with a zone of central necrosis, a mini left lumbotomy and evacuation of the hematoma were performed. The patient was discharged from the hospitalon the 23rd day of admission in stable general condition.Conclusion: The effect of anticoagulant therapy, especially in patients with existing risk factors, early diagnosis, and prompt therapy of spontaneous retroperitoneal hematomas is imperative to reduce mortality from this severe complication, in patients with the COVID-19 infection.
Keywords: retroperitoneal hematoma; COVID-19; arterial embolization